Cover crops for horseweed [Conyza canadensis (L.)] control before and during a soybean crop - Christenson, Andi Marie (Kansas State University, 2015)
Increasing numbers of herbicide-resistant weed species require alternative methods of weed suppression to be examined. This study quantified the interaction between various cover crop or herbicide systems and horseweed [Conyza canadensis (L.)] growth. Fall cover crops of winter wheat [Triticum aestivum (L.)], winter rye [Secale cereal (L.)], barley [Hordeum vulgare (L.)] and annual ryegrass [Lolium multiflorum (L.)] were seeded in November 2012 and 2013. Spring cover crop of oat [Avena sativa (L.)] was seeded in April 2013 or rye was seeded in March 2014. All cover crops were no-till seeded into grain sorghum stubble [Sorghum bicolor (L.) Moench]. Four herbicide treatments were fall or spring applied, with and without residual. The spring non-residual treatment was also applied to plots of winter rye. Cover crop plots were split and terminated with a roller crimper or glyphosate application prior to soybean [Glycine max (L.) Merr.] planting to determine the effect of termination method on treatment performance. Soybean was planted in June 2013 and May 2014 and mechanically harvested in October of both years. Horseweed density, biomass accumulation, and soybean yield data were quantified. Horseweed height, whole plant seed production, and seed subsamples were recorded in the untreated fallow control, winter wheat, and winter rye plots in 2014. Horseweed suppression by winter rye approached 90%, levels similar to suppression by herbicide systems. In both years, herbicide plots had less than half the horseweed biomass than any of the cover crop systems. In 2013, soybean yields in herbicide plots were at least 1,500 kg ha[superscript]-1, nearly more than double yields in cover crop plots. Soybean yields in 2014 were more consistent across treatments; barley and spring rye plots achieved yields equal to or greater than 2,000 kg ha[superscript]-1. Winter rye and winter wheat reduced horseweed seed production by 60% compared to the untreated fallow control, with no effect on individual seed weight. Seed production varied across plants, with the untreated control producing the greatest number of seeds. Cover crops were successful at reducing horseweed biomass, suppressing horseweed pressure, preserving soybean biomass, and protecting soybean yields when compared to a fallow untreated control.
Keywords: cover crops; soybeans; horseweed; Agriculture, General (0473); Agronomy (0285)